Development and validation of an ethical monopoly board game to teach bioethics to undergraduate medical students - Abeera Fatima; Usman Mahboob; Rehan Ahmed Khan; Saima Rafique (BMC Medical Education)
Abstract Background Ineffective teaching practices of bioethics are responsible for the rampant incidents of litigation, reports of misconduct, and complaints of unethical behaviors among medical professionals in various healthcare settings. There is a limited body of research on the implementation of innovative approaches for teaching ethical reasoning. One such approach is game-based learning, with board games emerging as a cost-effective and accessible tool for bioethics education. Aim To develop a board game to improve the teaching of bioethics and evaluate the effects of this board game on student satisfaction, engagement, and knowledge gain regarding bioethics. Methods The board game ‘Ethical Monopoly’ was developed and validated using a mixed-methods study design, following the steps of AMEE Guide 87. This study was conducted at the University of Lahore and Al-Aleem Medical College, from 2021–2023. The game’s content, design, and mechanics were developed using the combined results of a literature review and four focus group discussions with 16 undergraduate medical students and 11 faculty members. Situational Judgment tests were designed to familiarize the players with ethical dilemmas. A panel of 16 multidisciplinary expert judges evaluated the content validity of the Ethical Monopoly in a single round of the Delphi technique. The response process validity of the game was measured through observation and cognitive interviews with a group of eight undergraduate medical students. Results The Ethical Monopoly game was validated using a data collection instrument comprising 55 items on Game Rules (15 items), Game Design (four items), Game Cards (12 items), Game Relevance and Satisfaction (24 items). The content validity index, Scale-Level Content Validity Index Average (S-CVI/Ave) for board games was 0.93. Qualitative analysis of the cognitive interviews showed excellent response process validity. Students appreciated the user-friendly and colourful game design and the use of diverse and realistic scenarios in Situational Judgment tests. Conclusion Expert judges positively received an ethical monopoly prototype. It is a valid board game for teaching ethics with relevant learning objectives, attractive design, and game mechanics that are suitable for improving student motivation, interaction, and interest in learning bioethics.